Language Variations for Tourism Sectors around of English and Dutch Colonial Buildings: Sociolinguistics and Ethnolinguistics Studies - Inayatul Mukarromah; Sitti Zulaihah (Badan Pengembangan dan Pembinaan Bahasa, 2023)
The purpose of this research is to know the language variations through Sociolingustics and ethnolinguistics studies in the English heritage and colonial building areas. The approach used in this research is qualitative. The strategy of in this research designed by combining the qualitative research design from Lincoln (2003) with the descriptive qualitative research design from Permadi (2013). The research results in the emergence of code-mixing and code-switching in society. There are several languages are spread in those cultural heritage, such as: Chinese, Melayu, Arabic, Bugis, Maduresse and Indonesia. While, Banyuwangi has Oseng Language.Thus, the conclusion that it is necessary to understand the potential of the language used in society. In this case, not only the text but its use in social and cultural contexts because language does not only depend on its social aspects in the sense of how language is used in social contexts and culture but then how language finally can be an additinaol potention to support colonial tourism destination in Banyuwangi. AbstrakTujuan penelitian ini adalah untuk mengetahui variasi bahasa melalui pendekatan sosiolingusitik dan ethnolingusitik di Kawasan cagar budaya Inggrisan dan dua bangunan kolonial. Pendekatan yang digunakan dalam penelitian ini adalah kualitatif. Strategi yang digunakan dalam penelitian ini dirancang dengan mengkomibansi antara desain penelitian kualitatif dari Lincoln (2003) dan desain kualitatif deskriptif Permadi (2013). Hasil penelitian yang didapat bahwa terdapat campur kode dan alih kode dalam kehidupan di masyarakat. Ada beberapa bahasa yang tersebar dalam warisan budaya tersebut, seperti: Cina, Melayu, Arab, Bugis, Madura dan Indonesia. Dengan demikian, kesimpulan dalam penelitian ini adalah perlunya memahami potensi bahasa yang digunakan dalam masyarakat. Dalam hal ini, bukan hanya teksnya tetapi penggunaannya dalam konteks sosial dan budaya karena bahasa tidak hanya bergantung pada aspek sosial dan budaya saja tetapi bagaimana bahasa kemudian bisa dijadikan sebagai potensi tambahan untuk menunjang destinasi pariwisata kolonial di Banyuwangi.